2021
DOI: 10.20914/2310-1202-2021-1-86-93
|View full text |Cite
|
Sign up to set email alerts
|

Improving the massecuite crystallization in sugar production

Abstract: The article discusses the concepts of continuous vacuum apparatus operation: vertical VKT (VKT – Verdampfungs-Kristallisations-Turm) and horizontal cascade of VKH vacuum apparatus (VKH —horizontal vacuum pan) from BMA (Germany). The advantages and features of the vertical continuous vacuum apparatus VKT are shown, as well as the possibilities for increasing the efficiency of the product department of sugar factories. Thanks to the special design of the crystallization chambers, the low massecuite level above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…For example, the electrical energy stored in a capacitor at a high potential gradient, when it is discharged to the pulp, affects the cells of plant tissue within microseconds. At the same time, a significant power develops, many times, by about 3 orders of magnitude, exceeding the power of the action of a current with a voltage of 220 V. This causes a qualitative difference between such pulse action on plant tissue from the action of currents of low potential gradients [1][2][3][4][5]. A study by microphotography and direct visual observation of the dynamics of the action of an electric current on plant tissue cells and a comparison of our results with the data of other authors showed that the nature of the destruction of cell protoplasm by electric impulses is somewhat different than when exposed to an electric current with a voltage of 220 V. Treatment of plant tissue with an electric current low potential gradients leads to cell death, but the protoplasm does not disintegrate, but only loses the ability to retain juice in vacuoles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the electrical energy stored in a capacitor at a high potential gradient, when it is discharged to the pulp, affects the cells of plant tissue within microseconds. At the same time, a significant power develops, many times, by about 3 orders of magnitude, exceeding the power of the action of a current with a voltage of 220 V. This causes a qualitative difference between such pulse action on plant tissue from the action of currents of low potential gradients [1][2][3][4][5]. A study by microphotography and direct visual observation of the dynamics of the action of an electric current on plant tissue cells and a comparison of our results with the data of other authors showed that the nature of the destruction of cell protoplasm by electric impulses is somewhat different than when exposed to an electric current with a voltage of 220 V. Treatment of plant tissue with an electric current low potential gradients leads to cell death, but the protoplasm does not disintegrate, but only loses the ability to retain juice in vacuoles.…”
Section: Introductionmentioning
confidence: 99%